PENGEMBANGAN BUKU NUMER BOND BERBASIS ETNOMATEMATIKA BAGI CALON GURU SD - Astuti; Paustina Ngali Mahuze; Rival Hanip; Bernadetha Rizki Kaize; Dewi Puji Rahayu; Karlina Wong Lieung (Universitas Negeri Semarang, 2026)
Number bond is defined as a number bond meaning the separation of numbers into smaller values. There are similarities in the number bond principle with the calculations used by the Marind Tribe, Merauke, South Papua which is the background of the research. The purpose of the research is to develop a number bond book with an ethnomathematics approach with the intention of making mathematics easy to understand for students without eliminating the cultural elements and mathematical knowledge that students bring to school. The research uses the research and development (RnD) method through the planning and design stages. The results of the research show that the draft book consists of 3 chapters including chapter 1 containing the meaning, benefits, and how to teach number bond; chapter 2 describes ethnomathematics, the relationship between mathematics and culture, and the benefits obtained when studying ethnomathematics; and chapter 3 discusses the Marind Tribe, the Marind language, and Number bond in the Marind language.